Electromagnetic Technologies for Medical Diagnostics. Fundamental Issues, Clinical Applications and Perspectives - Crocco , Lorenzo (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The content of this Special Issue will highlight papers exploring non-commutative Fourier harmonic analysis, spectral properties of aperiodic order, the hypoelliptic heat equation, and the relativistic heat equation in the context of Information Theory and Geometric Science of Information.